Aggregation-induced white emission of lanthanide metallopolymer and its coating on cellulose nanopaper for white-light softening. Issue 6 (15th January 2020) - Zhang, Zhao; Chen, Yanxin; Chang, Hui; Wang, Yaoyu; Li, Xinping; Zhu, Xunjin
Abstract : AIE-active lanthanide metallopolymer coated on an optical haze nanopaper for application in soft-white-light emitting diodes (SWLEDs). Abstract : A series of metallopolymers containing two lanthanides (Poly-Eu-Tb, molar ratio of Eu 3+ /Tb 3+ = 1 : 1, 1 : 2, 1 : 4 and 1 : 8) have been synthesized via the coordination of Eu 3+ and Tb 3+ ions to terpyridine-based polymers (Poly). At a high concentration (1 mg mL −1 ) in DMF, Poly-Eu-Tb with an optimal Eu 3+ /Tb 3+ ratio (1 : 8) shows strong white light emission from the Poly backbone and Eu 3+ and Tb 3+ ions, but changes to very weak blue emission mainly from the Poly backbone when diluted to an extremely low concentration (0.1 mg mL −1 ). For typical aggregation-induced-emission (AIE) effects, a strong white light emission can be recovered along with the addition of 1, 4-dioxane to the diluted DMF solution. Moreover, Poly-Eu-Tb is uniformly dispersed on the surface of cellulose nanopaper (CNFs) via a simple solution coating process, giving a new flexible cellulose nanopaper Poly-Eu-Tb-CNFs. The new cellulose nanopaper characteristic of UV-excited white light emission shows excellent haze properties (haze value as high as 98%) and therefore could be applied as a substrate and light diffuser in the fabrication of soft-white-light emitting diodes (SWLEDs).